Investigation of evacuated direct flow tube solar collector using different types of solar relfector with water-bases nanofluid - Muhammad Iqbal, Ghazali (2013)
This is a study on determination of the effect of applying rear reflector and using distilled water-bases nanofluid as the working fluid to the evacuated tube solar collector located at Solar House, UMP Pekan. The objective of this project is to fabricate the bracket for Evacuated Tube Solar Collector (ETSC) and the systems, toNdevelop an efficient distilled water-based nanofluid solar collector by optimizing theNflow rate and collector tilt angle applicable to Pekan, and to compare the efficiencyNof Evacuated Tube Solar Collector using solar reflector and without solar reflector with distilled water and distilled water-based nanofluid as working fluid. TheNexperiment is conducted for the whole semester during Semester 2 2011/2012 andNSemester 1 2012/2013 although only specific date of valid data were used onNanalysis. The data obtained were analysed using theoretical analysis and plotted inNgraph to be discuss. From the experiments and calculations, the tilt angle of the solarNcollector were set to 8º and the flow rate of the working fluid is 2.7L/min. The solarNcollector efficiency is 43.52% using distilled water and its efficiency increase toN48.48% using 1% TiONnanofluid. For distilled water as the working fluid, theNcollector efficiency increase to 46.95% using aluminium reflector and increase toN44.28% using chrome reflector. For 1% TiO nanofluid as the working fluid which the collector efficiency is 48.48%, the collectorNefficiency increase to 49.52% using aluminium reflector and increase to 48.95% using chrome reflector.